Assessing participation of Central Asia and the South Caucasus countries in global and regional value chains - United Nations Economic; Social Commission for Asia; the Pacific; Yaroslava Babych; Davit Keshelava; Giorgi Mzhavanadze (Asia-Pacific Sustainable Development Journal, 2023)
Global and regional value chains offer opportunities for countries to participate in international production networks. While global and regional value chains participation indices exist for many developed countries, none of them cover Central Asian and the South Caucasus countries as a separate group. This study has created a comprehensive mapping of the global and regional value chains using intercountry input-output matrices. It contributes to the empirical literature on regional value chains by assessing the trade linkages between countries in the region and further defines the methodology to compare global and regional value chains participation at the industry level.